Multiple Soil Health Assessment Methods for Changing Agricultural Environment - Irina Gabriela Cara; Iuliana Motrescu; Gerard Jităreanu (Agriculture, 2026)
Soil is the foundation of resilient agricultural systems, yet its assessment remains a complex challenge due to its inherent variability across scales and management systems [...]